The educational and career backgrounds, managerial attitudes and satisfaction of college and university presidents - Lazo, Peregrino R. 1939-
This is an investigation of the college and university presidents with respect to their educational and career backgrounds, managerial attitudes, satisfaction, and inner- and outer-directed traits. The questionnaire was administered to presidents of colleges and universities in the four big cities of Greater Manila- Quezon, Pasay, Caloocan and Manila.
Mimeographed.
Thesis (Ph.D.)--University of the Philippines, Diliman.
Keywords: College presidents; Universities and colleges -- Administration